Wahabisme: Gerakan Revivalist Islam - Hendriyadi Hendriyadi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2020)
Wahhabism is one of the thougt in Islam whose existence and received muchattention from Muslims and even non-Muslims. This thought comes with a newpattern of understanding that is formally exclusive and carries the jargon ofrenewal. This thought is different from the Ahl alsunnah wa aljama'ah, both in thebelief, the pattern of da'wah, and other Islamic practice of amaliyah. Perspectivesand practices of other Muslim communities are judged as a religious distortion.This is where the Wahhabism felt superficial to do tajdid (reform)